Public Perceptions About Use of Siak River Fishermen In Tanjung Rhu District Fifty Pekanbaru Riau Province - Veny Fitriyani; Kusai '; Lamun Bathara (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2014)
This study was conducted on March 10th until March 20th, 2013. This study aims to determine the public perception about the use of the Siak River fishermen. The method used in this study is a survey method and determination of the respondents in this study is "Simple Random Sampling" by 24 respondents.The results of this research is the public perception of the use value of the Siak River and at the same level of perception, seen from the value of the public perception of the use of the Siak River 18 respondents (75%) stated that the Siak River is not safe to be used for the needs of fishing communities, at the same level of perception is in the category of less secure in the range of 1040-1455 which means the Siak River water can only be used for Industry, Fisheries, Transportation, Agriculture and Settlement.Keyword: the perception of the fishing community, the use of the Siak River